The Sofu Seamount Submarine Volcano Present in the Source Area of the October 2023 Earthquakes and Tsunamis in Japan - Toshiya Fujiwara; Kentaro Imai; Masayuki Obayashi; Kenta Yoshida; Noriko Tada; Koichiro Obana; Gou Fujie; Shigeaki Ono; Shuichi Kodaira (Geophysical Research Letters)
Abstract On 8 October 2023 (UTC), unique earthquakes occurred in the Izu‐Ogasawara Arc, Japan, in which the P‐ and S‐phases were barely visible and only the T‐phases were evident, followed by tsunamis that reached islands in the Izu‐Ogasawara Arc and a wide area of the Pacific coast of southwest Japan. Our estimated T‐phase source area coincides with the Sofu Seamount, which was previously unrecognized as an active submarine volcano. A bathymetric survey of the seamount conducted 1 month after the event revealed characteristics of the seamount with a caldera and a central cone. Compared to the bathymetry in 1987, the topography in the caldera had changed significantly such as a crater forming in the central cone. This seamount is likely to be an active volcano. The topographic changes on the caldera‐sized scale that occurred at the caldera can be explained as a source of the October tsunami.